Lonely robots - Logos M&M (Gent Stichting Logos, 2010)
On this seventh CD by the Logos M&M ensemble, a collection of newly built machines are presented individually. Where other CD releases give ample examples of what can be done when the robots come together to form an orchestra, this CD demonstrates the capacities of the new robots playing solo or as duos.The M&M orchestra is a professional group of dancers, performers, composers and musicians focusing on the interaction between man and machine, which has its permanent residence at the Logos Foundation. The machines are all electro-mechanical robots designed and built by Godfried-Willem Raes. On previous CDs in this series (LPD007: Automaton , LPD012 More Automats, LPD008 M&M , LPD013 Machine Orchestra, LPD014 Robodies, LPD018 Ancient Music and the CR-ROM LPRD001) we have documented earlier individual automata and some of their capacities as well as two albums devoted to new compositions for groups of robots.This CD reflects a momentary mid-2010 snapshot of the ongoing efforts of this unique ensemble to redefine musicianship. The adventure of this process can be followed by picking up some of our monthly concerts at the Logos Tetrahedron in Ghent as well as on this website.Building musical robots has been an ongoing activity in the Logos Labs since its very beginning in the late sixties. It is one of the many results of our investigations into the development of new tools for musical expression.All music on this CD is in the public domain. It can be freely distributed, even in public spaces, and can be broadcast provided the origin and the authors are always mentioned and given credit. MP3s of all tracks are freely available and can be downloaded from our site but if you want the best quality, we advise you to buy the original CD with a professionally printed booklet directly from us.